Perilaku Keuangan dan Kinerja Usahatani Sayuran di Kota Pontianak - Gabriella Dale Apriyani; Dewi Kurniati; Josua Parulian Hutajulu (Fapetrik-UMPAR, 2022)
As farm managers, farmers must apply financial behavior to ensure that their farms achieve good agricultural performance. Farmers in the city of Pontianak mainly grow horticultural products, especially vegetables. Therefore, the aims of this research are to determine the financial behavior level and vegetable cultivation performance level of farmers in Pontianak City, farmers' financial behavior affects the performance of vegetable farming in Pontianak City, and formulate efforts to improve the financial behavior of vegetable farmers. This study was conducted in the North Pontianak area of Pontianak City, West Kalimantan, with 90 farmers as respondents. Data were analyzed using descriptive, SEM-PLS with SmartPLS 3.0 tools and qualitative. According to data analysis, the financial behavior of vegetable growers in North Pontianak is classified as poor, and vegetable cultivation in North Pontianak is classified as poor. Additionally, the financial behavior of vegetable farmers in the North Pontianak region has a positive and significant impact on agricultural performance. Pontianak City A formalized effort to improve the financial behavior of vegetable farmers in the North Pontianak District is to provide socialization, training, mentoring, and strengthening with regard to financial reporting, particularly good financial management for growing vegetables.